2011
DOI: 10.5301/ejo.5000091
|View full text |Cite
|
Sign up to set email alerts
|

Acute Mountain Sickness and Retinal Evaluation by Optical Coherence Tomography

Abstract: In climbers with AMS, OCT was able to detect subtle increases in the peripapillary RNFL thickness and in some ONH measurements, even in absence of HACE and papilledema. These changes might be a sensitive parameter in physiologic acclimatization and in the pathogenesis of AMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…4500 m) have provided evidence for increased thickness of retinal nerve fibers and dilated, tortuous retinal vessels, it seems plausible to assume this as a contributing factor for the relative increase in TRT in the outer ETDRS subfields [13], [19], [30], [33]. One previous OCT study on retinal changes associated with high altitude exposure and acute mountain sickness showed no significant alteration in any of the ETDRS subfields [13]. However, subjects in this study were examined at an altitude of 247 m two weeks before and after returning from the expeditions in the Himalayas.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…4500 m) have provided evidence for increased thickness of retinal nerve fibers and dilated, tortuous retinal vessels, it seems plausible to assume this as a contributing factor for the relative increase in TRT in the outer ETDRS subfields [13], [19], [30], [33]. One previous OCT study on retinal changes associated with high altitude exposure and acute mountain sickness showed no significant alteration in any of the ETDRS subfields [13]. However, subjects in this study were examined at an altitude of 247 m two weeks before and after returning from the expeditions in the Himalayas.…”
Section: Discussionmentioning
confidence: 98%
“…Detailed quantitative analyses of macular changes at high altitude might be difficult to perform due to unique logistic challenges. Some studies circumvented this problem by recording changes several days after the exposure to altitude [13] [16] . However, measurements acquired any time after descent may not reflect the changes during acute exposure to high altitude related hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Fischer et al 8 adopted OCT and microdetermination to quantify changes in central retinal structure and function of 14 healthy subjects during rapid ascent to a high-altitude area (4559 m), and results found an increase of total retinal thickness. Ascaso et al 9 employed OCT to conduct complete ophthalmologic examinations for 12 healthy male mountaineers after four high-altitude expeditions in the Himalayas, and results indicated that average peripapillary RNFL thickness as well as the RNFL thickness of superior and temporal quadrants got a notable increase and that VIRA was much higher than that at baseline altitude. In this study, OCT was also used to determine the fine structure of retina such as thickness of the RNFL and GCL in the macula and the RNFL in the optic disc.…”
Section: Discussionmentioning
confidence: 99%
“…RNFL thickness was measured using the Stratus Optical Coherence Tomography (OCT) (Carl Zeiss Meditec, UK). OCT has been used extensively in many previous studies to assess RNFL thickness in vivo in various ophthalmic and neurologic diseases [17-19], as well as neurodegenerative disorders with frequent cognitive changes like schizophrenia [20], obstructive sleep apnoea syndrome [21], or acute mountain sickness [22], and has been widely tested in the elderly. Thinning of the RNFL has been noted with ageing, as demonstrated not only by OCT in different populations [23-27], but also by red-free photography [28], scanning laser polarimetry [29] and nerve fibre counts of post mortem human tissue [30].…”
Section: Introductionmentioning
confidence: 99%